Analysis of Family Life After The Death Of The Father In The Novel “ Saturday with Bapak” (Lembaga Pengembangan Kinerja Dosen, 2022)
The novel “ Saturday with Bapak” by Aditya Mulya. This book tells about the life journey of a family without a father figure. The father character in this book is told to die of cancer. The back-and-forth plot of this novel makes this novel even more interesting to read. Readers seem to be able to feel the story. Adhitya Mulya's success as a writer for a series of very touching messages about family was also followed and supported by the success of the film